EFFECT OF POSTERIOR PERICARDIOTOMY IN REDUCING FREQUENCY OF ATRIAL FIBRILLATION IN POST OPERATIVE CORONARY ARTERY BYPASS GRAFTING SURGERY (CABG) PATIENTS IN PUNJAB INSTITUTION OF CARDIOLOGY LAHORE - RAO, FJ; HASSAN , A; SARWAR , R; ATIF, G (Biological and Clinical Sciences Research Journal, 2024)
Postoperative atrial fibrillation (POAF) is a common complication following coronary artery bypass grafting (CABG), associated with increased morbidity, prolonged hospitalization, and higher healthcare costs. Posterior pericardiotomy, a surgical technique that facilitates the drainage of pericardial fluid into the pleural cavity, has been proposed as a preventive measure against POAF. Objective: To evaluate the effectiveness of posterior pericardiotomy in reducing the incidence of POAF in patients undergoing CABG at the Punjab Institute of Cardiology, Lahore, Pakistan. Methods: This randomized controlled trial included 94 patients undergoing CABG, randomized into two groups: Group A (posterior pericardiotomy) and Group B (control). Demographic data, POAF incidence, and postoperative outcomes were collected. Statistical analysis was conducted using SPSS version 20, with a p-value ≤0.05 considered significant. Results: The incidence of POAF was significantly lower in Group A (6.4%) compared to Group B (25.5%) (p=0.014). Group A also exhibited a shorter hospital stay (7.8 ± 1.4 days vs. 8.5 ± 1.6 days; p=0.021) and a lower incidence of pericardial effusion (4.3% vs. 21.3%; p=0.032). Both groups were comparable in baseline demographics and comorbidities. Conclusion: Posterior pericardiotomy significantly reduces the incidence of POAF, pericardial effusion, and hospital stay duration in CABG patients. These findings support its use as a safe and effective intervention to improve postoperative outcomes in resource-limited settings like Pakistan.